Stress and Fear of Covid-19 Infection among Nurses during the Covid-19 Pandemic, In Bengkalis District - Nurul Huda; Malissa Kay Shaw; Hellena Deli; Hsiu Ju Chang; Erwin Erwin; Desi Wahyuni (Universitas Pendidikan Indonesia, 2022)
Introduction: Nurses who provided care for patients infected with Covid-19 have experienced significant mental health issues due to increase workload, transfer infection, and limited psycho-social support access. Purpose: This study aimed to analyse the stress and fear of Covid-19 among nurses. Method: This study was an analytic correlation study that utilizes a cross-sectional approach. Between June and August of 2022, 70 nurses providing nursing care to Covid-19 patients were recruited from one referral hospital in Bengkalis, Riau. The DASS-S 42 and Fear of COVID-19 questionnaires were used to assess stress and fear of Covid-19 infection. The data were primarily analysed using multiple linear regression. Result: The nurse's mean fear of Covid-19 score is 18.87. The nurse's mean stress score is 8.6. This study found that stress is a predictor of fear of COVID-19 among nurses (p-value = 0.040). The stress variable affected 23.1 percent of the fear of the Covid-19 infection variable. Conclusion: Stress is predictor of fear of Covid 19 among nurses. Therefore, appropriate intervention to reduce stress is needed in order to decrease fear of covid-19 among nurses. ABSTRAKPendahuluan: Perawat yang memberikan perawatan pada pasien terinfeksi Covid-19 dapat mengalami masalah kesehatan mental yang dapat disebabkan oleh beban kerja yang tinggi, resiko terinfeksi, dan dukungan psiko-sosial yang terbatas. Tujuan: Penelitian ini bertujuan untuk menganalisis stres dan ketakutan terhadap Covid-19 pada perawat RSUD Mandau. Method: Penelitian ini merupakan analisis korelasi dengan pendekatan cross-sectional. Penelitian ini dilaksanakan pada bulan Juni hingga Agustus 200. Sampel pada penelitian ini berjumlah 70 orang perawat yang merawat pasien Covid-19 di RSUD Mandau. Pengumpulan data menggunakan DASS-S 42 dan fear of Covid-19 untuk mengukur stress dan ketakutan akan Covid-19. Analisis data yang digunakan adalah multiple regression. Result: Skor mean fear of Covid-19 Perawat adalah 18,8. Rerata skor stress perawat adalah 8,6. Hasil penelitian ini menunjukkan stress sebagai predictor fear of Covid-19 pada perawat (p-value = 0.040). Variabel stres mempengaruhi 23,1 persen variabel ketakutan terhadap infeksi Covid-19. Simpulan: Stress merupakan predictor dari fear of Covid-19 pada perawat. Oleh karena itu, intervensi yang tepat untuk menurunkan stress sangat dibutuhkan dalam rangka menurunkan ketakutan perawat akan fear of Covid 19.